Improvement of Power Quality Using Fuzzy Controlled D-STATCOM in Distribution System - B. Santhosh Kumar; K.B. Madhu Sahu; K.B. Saikiran; CH. Krishna Rao (Institute of Advanced Engineering and Science, 2018)
This paper investigates the problems associated with distribution system in terms of delivery of clean power and their solutions. Power quality has become a major issue in the present power system network. The network has mostly inductive nature. This draws more reactive power. This causes harmonics and voltage unbalance problems. So maintain the proper operation of interconnected power system, we are using one of the facts devices such as fuzzy controlled D-statcom. It provides suitable compensation and there by maintain proper power factor and also reduces harmonic contents. The simulation is taken out by MATLAB/SIMULINK and the result shows the effectiveness of GA (Genetic algorithm) simulation. Optimized Fuzzy controlled D-STATCOM for improvement of power quality.